Stent-Assisted Angioplasty of Spontaneous Bilateral Extracranial Vertebral Dissections under Intravascular Ultrasound Guidance - Won-Bae Seung (Case Reports in Neurology, 2018)
The authors here report a case of stent-assisted angioplasty under intravascular ultrasound (IVUS) guidance for the treatment of spontaneous bilateral extracranial vertebral artery (VA) dissection. A 47-year-old woman presented with spontaneous severe posterior neck pain. Examinations revealed bilateral extracranial VA dissection, which was thought to be the reason for her symptom. However, since the pain was gradually worsening even after sufficient medical treatment, she underwent stent angioplasty under IVUS guidance, following which her symptoms improved. We propose that stent placement under IVUS guidance is a safe and feasible method for treating extracranial VA dissections. Since the intravascular environment is seen in real time with IVUS, this technique is useful for confirming a true lumen and evaluating appropriate stent apposition. More clinical experience with this technique is required and mandatory, and devices with smaller diameters with improved trackability are essential for further introduction of IVUS into the field of endovascular neurosurgery.